Synthesis and characterization of a nanocomposite of goethite nanorods and reduced graphene oxide for electrochemical capacitors - Shou, Qingliang; Cheng, Jipeng; Zhang, Li; Nelson, Bradley J.; Zhang, Xiaobin (Journal of solid state chemistry, 2012)
We report a one-step synthesis of a nanocomposite of goethite (α-FeOOH) nanorods and reduced graphene oxide (RGO) using a solution method in which ferrous cations serve as a reducing agent of graphite oxide (GO) to graphene and a precursor to grow goethite nanorods. As-prepared goethite nanorods have an average length of 200nm and a diameter of 30nm and are densely attached on both sides of the RGO sheets. The electrochemical properties of the nanocomposite were characterized by cyclic voltammetry (CV) and chronopotentiometry (CP) charge–discharge tests. The results showed that goethite/RGO composites have a high electrochemical capacitance of 165.5Fg−1 with an excellent recycling capability making the material promising for electrochemical capacitors. The reduced graphene oxide sheets are decorated with goethite nanorods. The as-prepared composite exhibits a high electrochemical capacitance with good recycling capability, which is promising for supercapacitor applications. [Display omitted] ► Ferrous ions act as reductant of graphite oxide and precursor of goethite nanorods. ► Goethite nanorods are attached on both sides of the reduced graphene oxide sheets. ► Composite exhibits a high specific capacitance and a good recycling capability. ► Composite is promising for supercapacitor applications.